1980
DOI: 10.2134/agronj1980.00021962007200020018x
|View full text |Cite
|
Sign up to set email alerts
|

Residual Effects of Labeled N in Field Trials1

Abstract: Field trials utilizing 15N‐depleted fertilizer were conducted over a 6‐year period at two locations for the purpose of providing as complete an accounting as possible of N in the soil‐plant‐water system under conditions of irrigated agriculture. These trials permitted measurement of residual effects while continuing a constant rate of N application, and also after applications were discontinued. On Yolo fine sandy loam (Typic xerorthent) residual value of the previous year's fertilizer varied from negligible t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 4 publications
1
8
0
Order By: Relevance
“…We found that the residual 15 N-labeled urea in soil was largely present as NO 3 --N and accounted for 92.5% and 91.3% in the FP and OPT treatments, respectively. This was in agreement with the result of Broadbent (1980), who suggested that residual N fertilizer mainly remained as inorganic N in the first season. The significantly (P < 0.05) higher NO 3 --N accumulated down to 40 cm in the FP (129.8 kg N/ha) compared to the OPT treatment with 61.4 kg N/ha, where it cannot be easily absorbed by the crop.…”
Section: Accumulation and Loss Of 15 N-labeled Ureasupporting
confidence: 93%
“…We found that the residual 15 N-labeled urea in soil was largely present as NO 3 --N and accounted for 92.5% and 91.3% in the FP and OPT treatments, respectively. This was in agreement with the result of Broadbent (1980), who suggested that residual N fertilizer mainly remained as inorganic N in the first season. The significantly (P < 0.05) higher NO 3 --N accumulated down to 40 cm in the FP (129.8 kg N/ha) compared to the OPT treatment with 61.4 kg N/ha, where it cannot be easily absorbed by the crop.…”
Section: Accumulation and Loss Of 15 N-labeled Ureasupporting
confidence: 93%
“…That explanation would presumably also apply to the apparent persistence of labelled nitrate in soil which was observed by Broadbent and Carlton (1978) at the end of the second season from the time of fertilizer application. Broadbent (1980) found little evidence of remineralization of the immobilized fertilizer-N and concluded that the residual fertilizer-N that is taken up by a subsequent crop will mostly have remained as inorganic N in the root zone. Incorporation of inorganic 15N into the stable fraction of organic matter can occur within two months of fertilizer application (Kai et al, 1973) such that the extent of remineralization of immobilized fertilizer-N depends on whether the fertilizer-N is immobilized in a fast or slowly decomposing substrate in soil (Bergstr6m, 1987).…”
Section: Residual Fertilizer-nmentioning
confidence: 99%
“…Therefore, the efficiency with which agricultural crops utilize such fertilizers is of agroeconomic importance. When fertilizer-N is affordable, large application rates often increase the amounts of N remaining in soil (Broadbent, 1980;Broadbent and Carlton, 1978;Olson, 1980) and those leached beyond the root zone (Baker and Johnson, 1981;Bergstr6m and Brink, 1986). Thus the fate of fertilizer-N following addition to soil, is also important from an environmental viewpoint (Bergstr6m and Brink, 1986;Gustafson, 1983;Olson, 1980;Schuman et al, 1975).…”
Section: Introductionmentioning
confidence: 99%
“…The potential to design experiments using depleted 15 N are illustrated in studies by Broadbent (1980), Patrick et al (1984), Porter (1995), Russelle et al (1981), and others. An example where depleted 15 N was used is that by Porter (1995), where he evaluated N-fertilizer carryover, leaching, and uptake under continuous irrigated corn (Zea mays L.) on a Weld silty clay loam (fine, montmorillonitic, mesic Aridic Paleustoll) near Akron, Colorado.…”
Section: Depleted 15 Nmentioning
confidence: 99%
“…Broadbent (1980), using depleted 15 N-labeled fertilizer, measured residual effects while continuing a constant rate of N-application. Rates of N application were 0, 90, 180, and 360 kg N ha Ϫ1 .…”
Section: Fertilizer N Dynamics and Soil Biologymentioning
confidence: 99%